Personal income in New Zealand at the current stage of economic development - I. V. Mitroshin (Вестник университета)
Any socio-economic processes occurring in the country and world have an impact on the standard of living of the population. There are many indicators that determine the standard of living of citizens, among which we can highlight the income of people as the main component of their financial well-being. In a period of global political and economic upheavals, the relevance of the topic of human quality of life is beyond doubt. During the economic war organised by the West against Russia, the countries participating in this war are of interest. These include New Zealand, although it is clear that due to the distance from Russia and weak economic ties between the countries, there will be no significant mutual influence of the sanctions restrictions. The study has analysed the income of the population of New Zealand over the past 10 to 15 years, considering differentiation by various categories, such as geographical location, qualification, and source of income. The analysis has showed a certain increase in the income and, accordingly, in the standard of living of the country’s population in the period under review. An insignificant impact on this indicator of restrictive measures during the COVID-19 pandemic is revealed, however, with the certain social policy of the state, fluctuations in the income of citizens during this period were hardly noticeable. Their assessment by sources has reflected the significant share of small businesses in the country’s economy, which shows a high degree of liberalisation of the national economy of the state. The analysis of the citizens’ incomes by geographic regions has revealed a significant impact of urbanisation on the standard of living of the New Zealand’s population, which is a global trend.